PERLINDUNGAN HUKUM TERHADAP KORBAN MODUS LOVE SCAM DALAM SITUS KENCAN ONLINE DI INDONESIA - Sephia Putri, Ni Kadek Dinda; Saraswati, Putu Sekarwangi (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2024)
The phenomenon of globalization influencing the development of human civilization, along with the increasing role of the internet and social media in daily life, has led to new challenges such as the rise in love scam cases utilizing technology for criminal activities. The legal conditions in Indonesia, which currently lack specific regulations to address love scam crimes, underscore the need for in-depth research on legal protection for victims of love scams on online dating sites. This study formulates the research problems: 1) legal regulations concerning victims of love scam schemes in Indonesia, and 2) legal protection for victims of love scam schemes on online dating sites. The research employs a normative legal research method by adapting legislative and conceptual approaches, with legal material collection techniques using literature study methods involving prescriptive analysis. Legal regulation regarding perpetrators of love scams in Indonesia faces normative conflicts between Article 378 of the Criminal Code (KUHP) and Article 28 paragraph (1) of the Electronic Information and Transactions Law (UU ITE), leading to legal uncertainty. Law enforcement is challenged in determining which article is more appropriate for prosecuting love scam perpetrators. Therefore, it is necessary to protect victims through education efforts, physical and security protection, fair and transparent legal processes, protection from threats, post trauma recovery, assistance from relevant experts, and protection of victims' identities.